2015
DOI: 10.1111/jch.12649
|View full text |Cite
|
Sign up to set email alerts
|

Nitric Oxide Contributes to Vasomotor Tone in Hypertensive African Americans Treated With Nebivolol and Metoprolol

Abstract: Endothelial dysfunction is more prevalent in African Americans (AA) compared to whites. We hypothesized that nebivolol, a selective β-1 antagonist that stimulates NO, will improve endothelial function in AA with hypertension when compared to metoprolol. In a double-blind, randomized, cross-over study, 19 AA hypertensive subjects were randomized to a 12-week treatment period with either nebivolol 10mg or metoprolol succinate 100mg daily. Forearm blood flow (FBF) was measured using plethysmography at rest and af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 53 publications
(125 reference statements)
0
14
0
Order By: Relevance
“…Blood pressure medications have also been explored, yielding mixed results. Specifically, nebivolol, a β 1 -selective receptor blocker with NO-potentiating effects, demonstrated efficacy in improving endothelial function 89, 90. Conversely, metoprolol, a β 1 -selective receptor blocker, and spironolactone, an aldosterone antagonist, had minimal to no effects on endothelial function 91, 92…”
Section: Clinical Trials and Endothelial Functionmentioning
confidence: 99%
“…Blood pressure medications have also been explored, yielding mixed results. Specifically, nebivolol, a β 1 -selective receptor blocker with NO-potentiating effects, demonstrated efficacy in improving endothelial function 89, 90. Conversely, metoprolol, a β 1 -selective receptor blocker, and spironolactone, an aldosterone antagonist, had minimal to no effects on endothelial function 91, 92…”
Section: Clinical Trials and Endothelial Functionmentioning
confidence: 99%
“…Ten clinical trials and 689 patients were included in this analysis, of which 128 patients were randomized in one double-blind, parallel-group design trial, 90 randomized in three double-blind crossover design trials, 214 randomized in two single-blind, parallel-group design trials, 187 randomized in three-open design trials, and 70 randomized in one unreported design trial (Table 3). The patients received nebivolol, ranging from 5 mg [20] to 10 mg [13], or control antihypertensives including β-blockers (metoprolol [13,21], carvedilol [20,22], atenolol [14,[23][24][25], bisoprolol [26]) or other antihypertensives (olmesartan [11], nifedipine [24], amlodipine [24], telmisartan [24], perindopril [24]). One of these trials compared the effects of combined use of nebivolol and enalapril with the combination of atenolol and enalapril [14], and another showed an effect difference between nebivolol and atenolol on the background of 2.5 mg bendrofluazide [25].…”
Section: Characteristics Of Included Trialsmentioning
confidence: 99%
“…The treatment time ranged from 2 [14] to 48 [24] weeks. In two trials [13,25], FBF measurement, other than FMD, was obtained using a venous occlusion strain gauge plethysmograph to evaluate the endothelial function. The characteristics of the included trials are shown in Table 3.…”
Section: Characteristics Of Included Trialsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have read with great interest the recently published article by Neuman and coworkers 1 in which they hypothesized that nebivolol, a selective b 1 -antagonist that stimulates nitric oxide (NO), improves endothelial function in African Americans with hypertension when compared with metoprolol. In that well-designed study, the authors found evidence for NO bioavailability at rest during treatment with both nebivolol and metoprolol succinate in hypertensive African American patients, with a clear trend for a greater contribution of NO during nebivolol therapy.…”
mentioning
confidence: 99%